Using cellular fitness to map the structure and function of a major facilitator superfamily effluxer. Issue 12 (22nd December 2017) - Perez, Anisha M; Gomez, Marcella M; Kalvapalle, Prashant; O'Brien‐Gilbert, Erin; Bennett, Matthew R; Shamoo, Yousif
Abstract: The major facilitator superfamily (MFS) effluxers are prominent mediators of antimicrobial resistance. The biochemical characterization of MFS proteins is hindered by their complex membrane environment that makes in vitro biochemical analysis challenging. Since the physicochemical properties of proteins drive the fitness of an organism, we posed the question of whether we could reverse that relationship and derive meaningful biochemical parameters for a single protein simply from fitness changes it confers under varying strengths of selection. Here, we present a physiological model that uses cellular fitness as a proxy to predict the biochemical properties of the MFS tetracycline efflux pump, TetB, and a family of single amino acid variants. We determined two lumped biochemical parameters roughly describing K m and V max for TetB and variants. Including in vivo protein levels into our model allowed for more specified prediction of pump parameters relating to substrate binding affinity and pumping efficiency for TetB and variants. We further demonstrated the general utility of our model by solely using fitness to assay a library of tet(B) variants and estimate their biochemical properties. Synopsis: A physiological model uses cellular fitness as a proxy to predict the biochemical properties of major facilitator superfamily tetracycline efflux pump, TetB, and a family of variants. The model incorporates drug diffusion, growth inhibition by the drug, and active drug transport by TetB. Cellular fitness as a function of drug concentration is modeled to reveal biochemical properties of TetB and variants relating to V max and K m . A mathematical approximation allows for the decoupling of changes in variant cellular fitness due to substrate binding affinity and pumping efficiency after incorporation of protein levels. Desirable candidates from a plasmid variant library are quickly screened using only cellular fitness as a function of drug concentration. The model results are in good agreement with current knowledge of MFS transporter structure‐function relationship. Abstract : A physiological model uses cellular fitness as a proxy to predict the biochemical properties of major facilitator superfamily tetracycline efflux pump, TetB, and a family of variants. The model incorporates drug diffusion, growth inhibition by the drug, and active drug transport by TetB.